The Survival and Continuity of Islamic Boarding School in the Era of Changes - Ahmad Royani; Hepni Hepni (Jurnal Penelitian, 2022)
The fast change requires the ability of Islamic boarding school to respond fast, rightly and adaptively. Using qualitative phenomenology, this study tries to see the phenomenon of changes faced by Islamic Boarding School of Nurul Islam Jember. The result of this study is that the adaptation of changes is done by the model of safeguarding and conserving the positive local values (localities) and useful for the Islamic boarding school. As agent of change, the Islamic boarding school of Nurul Islam participates in the societies’ change actively. Besides that, the cancelling of personality is to prepare santri to have the religion and non-religion knowledge to be Islamic human who can apply their knowledge. The personality built by Islamic boarding school of Nurul Islam is able to face and respond the changes without ignoring the morals (Akhlaq). In fact, the Islamic boarding school of Nurul Islam tries to integrate the formal school system and Islamic boarding school system to build the capable generations. The Islamic boarding school with soft skill and the formal school with life skill will be the solution of adaptive education in the era of changes.